Wild Plants used as Vegetable in Rupandehi District of Nepal and their Ethnomedicinal Importance - Singh, Anant Gopal; Singh, M.P.; Tewari, D.D. (Journal of Natural History Museum, 2015)
Consumption of green plant is a major source of vitamins and micronutrients for people using only vegetarian diets rich in carbohydrates. In rural areas where vegetable cultivation is not practiced and market supplies are not organized, local inhabitants depend on cultivated or wild indigenous vegetables for enriching the diversity of food. Knowledge of such food is part of traditional knowledge is largely transmitted through participation of individuals of households. The purpose of this study was to documentation of wild plants used as vegetables by the people of Rupandehi district, western Nepal. This paper revealed total 43 plant species belong to 36 genera under 29 families of vascular plants. J. Nat. Hist. Mus. Vol. 26, 2012: 111-125